Confini, migrazioni e diritti umani - Ambrosini, Maurizio; D'Amico, Marilisa; Perassi, Emilia (Milano University Press, 2022)
Although there had long been pressing demands to limit international migration, the terrorist attacks of 11 September 2001 marked an emblematic turning point in national border policies. The new century ushered in renewed efforts by national governments, and hence European policymakers, to re-instate stricter controls on trans-border mobility, even at the cost of violating international agreements and compromising commitments to the protection of human rights. The theme of borders has also been a domain of inquiry for academia and the scientific community. Various scientific disciplines have pooled resources and initiated dialogue with the larger society on issues such as boundaries, migrations, and human rights. This volume is the fruit of an initiative by the UNIMI Migration and Human Rights Research Centre and offers the thoughts and insights of a number of authors, contributing a range of disciplinary perspectives to bear on this critical issue of our times.